Spatio-temporal variability of the trophic ecology of the cockle (Cerastoderma edule) in an estuarine bay: the Baie des Veys (France) - Varin, Laura (2023)
Estuaries are located at the interface between oceans and rivers. These ecosystems are submitted to spatio-temporal variations of environmental parameters which can affect benthic communities. Seasonally, during three years, cockles (Cerastoderma edule) were collected from three stations in the Baie des Veys (Normandy, France). Their isotopic compositions were observed in function of several factors (year, season, station and size class) and combined with their potential food sources [i.e. particulate organic matter (POM), riverine particulate organic matter (RPOM) and microphytobenthos (MPB)]. Stable isotope analysis, based on a set of carbon and nitrogen ratios, was applied to assess differences in cockles’ diet. Permutation analysis of variance (PERMANOVA) was used to test the effects of factors on the cockles’ flesh composition and food sources were investigated using a stable isotope mixing model (SIAR). Results showcase no differences about δ13C and δ15N ratios between juveniles and adults neither differences between stations and between years. In contrast, a measurable effect of season on cockles’ isotopic composition (p<0.001) as well as a significant interaction between season and year was highlighted. The seasonal differences of stable carbon isotope ratios in cockles result from variability of food intakes. RPOM is considered like an alternative food source because it did not contribute enough to the cockles’ diet unlike POM and MPB. Food sources contributions showed that MPB is preferentially consumed because, on average, 60% of cockle production originated from MPB during the study period. There is an inter-annual variation of isotopic signatures of individuals probably caused by physiological responses to variations of environmental parameters. Seasons are different (temperature, luminosity, pluviometry), affect sources' signature and consequently cockles' signature vary also.